The Comprehensive Review of Deviated Septum: Anatomy, Diagnosis, and Treatment Approaches - Zuzanna Kudas; Mateusz Górka; Weronika Stec; Anna Wojtkiewicz; Magda Piekarska; Krzysztof Szerej (Quality in Sport)
Deviated septum, a common nasal structural abnormality, often leads to symptoms like nasal obstruction, sinusitis, and sleep disturbances, impacting respiratory function and quality of life. This clinical review emphasizes the critical role of septoplasty in the treatment of nasal septum deviation (NSD). While the nasal septum's anatomy is essential for proper airflow, deviations can cause significant issues, particularly in severe cases.